Avaliação de doses em órgãos radiossensíveis expostos durante exames de tomografia computadorizada por feixe cônico e radiografia panorâmica - Heiden, Katia Regina (2016)
Panoramic radiograph and cone beam computed tomography (CBCT) are imaging methods widely used in dentistry because they provide an overview of dentomaxillofacial complex, being important in the diagnosis and treatment of lesions that affect this region. Panoramic radiograph is considered a low-dose procedure and CBCT presents lower doses when compared with computed tomography (CT). Although low, the doses from these imaging methods expose radiosensitive organs, such as thyroid and salivary glands, to the risks of ionizing radiation. Knowing the levels of radiation these organs are exposed is important to select the appropiate imaging method and exposure parameters to be used, reducing the risks associated with ionizing radiation, according to the principle of radioprotection ALARA (As Low As a Reasonably Achievable). The aim of this study was to evaluate the absorbed doses by these radiosensitive organs during the course of panoramic radiographs and CBCT examinations, using different exposure parameters. Thermoluminescent dosimeters (TLDs) were inserted into an anthropomorphic phantom Alderson Radiation Therapy (ART) to identify the absorbed doses by the thyroid and salivary glands, in a panoramic x-ray unit and two CBCT units with different protocols. Absorbed doses ranged from 0.01 to 0.22 mGy in the thyroid and 0.26 to 2.96 mGy in the salivary glands. Doses in CBCT varied according to the selected protocol, but were higher than the dose of a panoramic radiograph. The CBCT protocols that used long exposure times, considered as high-resolution protocols, resulted in higher doses compared to protocols that used low exposure times. Protocols that used fields of view (FOVs) higher, exposed the thyroid at higher levels of radiation. Based on the results obtained, it can be concluded that CBCT should only be requested if the diagnostic information can’t be obtained through the panoramic radiograph and the appropriate choice of technical factors essential to reduce the radiation dose during examinations CBCT.